Odpowiedź :
I1-√2 I : I4-3√2I =
=(-1+√2 ) :( -4+3√2) =
=[(√2-1)(3√2+4)]:[(3√2-4)(3√2+4)]=
=[6+4√2-3√2-4]:[18-16]=
=[2+√2]:[2]=1+√2:2
=(-1+√2 ) :( -4+3√2) =
=[(√2-1)(3√2+4)]:[(3√2-4)(3√2+4)]=
=[6+4√2-3√2-4]:[18-16]=
=[2+√2]:[2]=1+√2:2
=(√2-1):(3√2-4)=[(√2-1)(3√2+4)]:[(3√2-4)(3√2+4)]=
=[6+4√2-3√2-4]:[18-16]=
=[2+√2]:[2]=1+(√2/2)
wyrazenie w wartosci bezwzglednej, przez wyrazenie w wartosci bezwzględnej musi dać wartość dodatnią lub zero!!
=[6+4√2-3√2-4]:[18-16]=
=[2+√2]:[2]=1+(√2/2)
wyrazenie w wartosci bezwzglednej, przez wyrazenie w wartosci bezwzględnej musi dać wartość dodatnią lub zero!!